Detail in contemporary residential architecture - McLeod, Virginia (London : Laurence King Publishers, 2007)
Architectural detailing makes a building unique and an architect outstanding. This book provides analysis of both the technical and the aesthetic importance of details in the development of contemporary domestic architecture from 2000 to 2005. Featuring many of the world's most highlyacclaimed architects, the book presents over 50 of the most recently completed and influential house designs. For each house there are color photographs, plans of every floor, sections and elevations, and numerous construction details. The book also features in-depth information for each project, including the size, the client, the architectural project team, main consultants, and contractors. With CD-ROM.
Keywords: Architecture, Domestic; Architecture -- Details; Residential architecture